Modular Ti-6Al-4V system for in vitro optimization of implant materials - von Heckel, Charlotte; Walles, Heike; Hasemann, Georg; Krüger, Manja (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTitanium is a widely used biomaterial for implants. Research is focused on optimizing titanium by modifying its surface structure and porosity to prevent complications such as implant loosening or foreign body reactions. However, changes to implant materials necessitates preclinical testing, often involving animal testing, which gives rise to ethical concerns. This underscores the significant demand for test systems that can reduce time and costs. Although in vitro models can provide valuable initial insights into the biological evaluation of biomaterials and help reduce the need for animal experiments, dedicated test systems for biomaterial evaluation remain limited.MethodsIn our work, we developed modular 3D porous stacked models using Ti-6Al-4V sheets with different structural designs. These models are used to demonstrate the migration of primary human fibroblasts into the implant through fluorescence microscopy and investigate the effects of pore size. In addition, Ti alloy sheets with slots were polished and ground (1,200 grid SiC) to examine differences in cell adhesion and migration for different surface properties.ResultsThe MTT results indicate similar cell growth on the different patterns and surface conditions, which suggests the use of more biomimetic structures in the future.DiscussionConsequently, our model serves as a screening system for optimization of porosity and surface conditions of implant materials, which contributes to early-stage in vitro biocompatibility and cell migration studies.